If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 2n = 7 + n Solving 9 + 2n = 7 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 9 + 2n + -1n = 7 + n + -1n Combine like terms: 2n + -1n = 1n 9 + 1n = 7 + n + -1n Combine like terms: n + -1n = 0 9 + 1n = 7 + 0 9 + 1n = 7 Add '-9' to each side of the equation. 9 + -9 + 1n = 7 + -9 Combine like terms: 9 + -9 = 0 0 + 1n = 7 + -9 1n = 7 + -9 Combine like terms: 7 + -9 = -2 1n = -2 Divide each side by '1'. n = -2 Simplifying n = -2
| 2+3a=6a-7 | | t=2s+3.75 | | 2(x+2)+2x=x+7 | | 4x-8x+6=-18 | | 4q+3q-4q-2q=15 | | 21b=b+25 | | 9-5w=12-6w-7 | | 5y+2y-6y+y+2y=16 | | 4x-8+6=-18 | | (x*x+14x+49)(x*x-196)=0 | | 3(x+1)+y=7 | | 2t+t-t=20 | | x+x+1+x+2=54 | | 10-(5-2x)=2-5(5+2x) | | 3a^3+15a^2-42x=0 | | 17t-13t=20 | | 11a-3a=8 | | 2x=4(6-x) | | 7y-4=33-6y | | (3x-4)(x-9)=5 | | (y-5)(y-9)=15 | | a-2n=-10 | | 5(-2x-4)-3(4x*5)=47 | | 4=-2(3p+25) | | 4(6+5a)=-116 | | 5-2(3x-4)=13 | | 2b-3=19 | | p^2-18=3p | | a^2+18=-9a | | 4y^4-2y^3= | | x+12=189 | | 8v+7=1+7v |